PENGARUH INFORMASI LAPORAN ARUS KAS, DEVIDEND PAYOUT RATIO (DPR), ECONOMIC VALUE ADDED (EVA) TERHADAP VOLUME PERDAGANGAN SAHAM DI BURSA EFEK INDONESIA (Studi Pada Perusahaan LQ 45 Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2010-2013) - Stifany Ayuningrum; Hardi -; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study is to find out the relationship between cash flow statement, devidend payout ratio and economic value added toward the trading volume stock at LQ 45 companies which are listed at Indonesia Stock Exchange in the year 2010-2013. The population in this study is all LQ 45 companies listed on the Indonesia Stock Exchange (IDX) 2010-2013. The population is as much as 45 companies. The sample size is as much as 24companies, analysis of data using multiple regressions. Based on the results obtained from the results of the data analysis, it can be concluded that the Cash flow from operation and cash flow from funding has no significant effect on Stock trading volume, Economic value Added does not have a significant effect on the Stock trading volume, Cash flow from investment has a significant effect on stock trading volume and last Devidend payout ratio has significant effect on Stock trading volume.Keywords: Cash Flow Statement, Devidend Payout Ratio (DPR), Economic Value Added (EVA),and Stock Trading Volume.